2018
DOI: 10.1093/ons/opy259
|View full text |Cite
|
Sign up to set email alerts
|

A Connectomic Atlas of the Human Cerebrum—Chapter 5: The Insula and Opercular Cortex

Abstract: In this supplement, we build on work previously published under the Human Connectome Project. Specifically, we show a comprehensive anatomic atlas of the human cerebrum demonstrating all 180 distinct regions comprising the cerebral cortex. The location, functional connectivity, and structural connectivity of these regions are outlined, and where possible a discussion is included of the functional significance of these areas. In part 5, we specifically address regions relevant to the insula and opercular cortex. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…The comparably stronger esfMRI effect in monkeys and humans from stimulating auditory cortex seen in the PHG, which was stronger than certain hippocampal subregions, suggests an equally indirect auditory cortical projection to the hippocampal memory circuit across these species. This observation is not inconsistent with impressions from human resting-state connectivity, including ultra-high-resolution data 33,34 . The current findings challenge the notion that monkeys have a less direct auditory effective interconnectivity with the MTL memory system than humans.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The comparably stronger esfMRI effect in monkeys and humans from stimulating auditory cortex seen in the PHG, which was stronger than certain hippocampal subregions, suggests an equally indirect auditory cortical projection to the hippocampal memory circuit across these species. This observation is not inconsistent with impressions from human resting-state connectivity, including ultra-high-resolution data 33,34 . The current findings challenge the notion that monkeys have a less direct auditory effective interconnectivity with the MTL memory system than humans.…”
Section: Discussionsupporting
confidence: 71%
“…The macaque vlPFC ROI effects were also statistically indistinguishable across the two hemispheres (no significant Hemisphere effect). The ROIs showed a trend towards a differential fMRI response ( F 2,33 = 3.04, p = 0.054), and the planned post-hoc comparisons identified stronger esfMRI activity in the FOP over areas 45 and 44 in that order (all p < 0.002, Bonferroni corrected; Fig. 4A-B).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…[67] Thus, a study specifically designed to adequately resolve white matter connectivity at such small spatial scale, particularly in the complex mid-temporal region could reveal connectivity differences between A1 and the insula. [68] Third, as has been done in misophonia, interoceptive awareness, which is localized to the insula, should be assessed in ASMR, for instance by use of the body consciousness questionnaire. [46,48] We predict it would be heightened.…”
Section: Testing the Hypothesismentioning
confidence: 99%
“…The ventral dysgranular insula has extensive connections with the amygdala, anterior part of cingular cortex, pre-SMA, portions of the PMV and PPC, ventral striatum, lateral hypothalamus, and periaqueductal gray [17]. Anatomically, dorsal middle insula and SMA [22], inferior frontal gyrus and SMA have direct connection reciprocally by the frontal aslant tract [23]. In clinical studies, analysis of functional coupling during clonic activities in SEEG in two patients with tonic posturing revealed that the middle and posterior insula were more strongly connected to SMA/pre-SMA, while the patient with hypermotor behaviors showed significant functional coupling between the ASG and anterior mesial frontal areas [9].…”
Section: Anatomical Electroclinical Correlationsmentioning
confidence: 99%